(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To characterize the clinical and epidemiological profile of patients undergoing lower limb amputation in a public hospital in southern Piauí state, Brazil. Method: Retrospective and descriptive study, with document analysis and quantitative approach. Data collection took place in July and August 2021, using an instrument developed by the researchers. Data were processed using the statistical software Statistical Package for Social Sciences, version 20.0. Results: The sample consisted of 70 patients with a mean age of 65.59 years, most of them male (61.4%), brown (88.6%), married (48.3%), retired (42.9%), coming from other cities of Piauí (87.1%). Most patients (47.1%) had a comorbidity at the time of amputation, with diabetes mellitus (34.3%) being the most prevalent, followed by systemic arterial hypertension (12.9%). Diabetes was the main cause of amputation (48.6%), being the transfemoral level (42.9%) the most affected. All procedures were performed on an emergency basis, and most hospitalizations (94.3%) progressed to discharge. Conclusion: The findings of this study reveal that people with diabetes, males, and the elderly were the individuals who most underwent amputation, with the transfemoral level being the most performed.